It takes a village: The vital role of community organizations in enhancing fistula patient identification, referral, and reintegration in Kenya - Mohamed, Habiba C.; Pollaczek, Lindsey (Nepal Journal of Obstetrics and Gynaecology, 2018)
Action on Fistula, Kenya, is a multi-year initiative (2014-present) focused on expanding access to fistula care and building the national capacity for fistula treatment, training, and community mobilization. Led by Fistula Foundation in partnership with the Ministry of Health, public and private hospitals, and community-based outreach organizations, over 4,000 fistula repair surgeries have been performed at six hospitals throughout the country. One of key factors in driving the success of the program is the use of extensive community outreach networks to increase patient referrals, improve community awareness and knowledge of fistula, and facilitate reintegration for women following fistula repair surgery. Through this community initiative, women from all of Kenya’s 47 counties have been treated and over 85% of patients have come through the AOF partner outreach efforts. Varied mobilization strategies have been utilized to maximize results, including training and engagement of community outreach workers, media engagement through radio spots and live talk shows, partnerships with health facilities and training of health center staff, community outreaches and rallies, and the use of “Kick Fistula out of Africa” soccer team to raise awareness and help destigmatize the condition. In the second phase of the initiative, reintegration programs were also initiated by the same community organizations and enhanced follow-up measures were put in place to assess longer-term outcomes for continence status, social and psychological wellbeing, and economic health.